Climate change in the Westfjords, Iceland : a local perspective of a global problem - Bannan, Deirdre Patricia 1990- (2022)
Ritgerðin er lokuð til 10.03.2023 Climate change is one of the most pressing issues of our time. Climate has fluctuated considerably over Earth’s history, however we seem to be now in a period of climate warming that is novel in its anthropogenic causes and impacts on human livelihoods in manifold ways. This warming is predicted to have many global consequences, including ecosystem damage, spread of disease and sea level rise, which gives rise to investigate the impact of these changes. Iceland, located in the middle of the North Atlantic Ocean just south of the Arctic Circle, is experiencing increasing risks to its physical, biological and social systems. This study aims to analyse and communicate climate change from a local perspective, focusing on the Westfjords region in north-western Iceland, by assessing the changes in air temperature and precipitation, and evaluate their potential impact on physical, biological, and social systems. Existing temperature and precipitation data were collected from weather stations located around the Westfjords. These were used to model trends of climate change in the region at an unprecedented resolution. The results show that the period 2001-2020 has been warmer than a 1961-1990 reference period for almost every month of every year. Furthermore, that warming has been more pronounced in the winter months. A pattern of seasonality that was detectable at the beginning of the twentieth century is notably reduced at the beginning of the twenty-first century. Precipitation analysis suggests that precipitation has increased during 1991-2020 compared to 1961-1990. These detected patterns mirror some of the major predictions about climate change but also highlight the importance of gaining further local perspectives. The Westfjords region should adopt careful management and adaptation strategies for the impacts of climate change going forward. Loftslagsbreytingar eru eitt af mest aðkallandi málefnum líðandi stundar. Loftslag hefur í gegnum jarðsöguna sveiflast töluvert, þær ...